STRATEGI MANAJEMEN KONFLIK DALAM MENINGKATKAN KINERJA TIM PENDIDIK DI PAUD - Mutoharoh, Mutoharoh; Mu`awwanah, Uyu (Jurnal Visi Ilmu Pendidikan, 2025)
Conflict is an inevitable phenomenon in organizations, including Early Childhood Education (PAUD) units. Differences in background, values, and goals among educators often serve as the primary triggers for conflict, which, if not managed properly, can negatively impact the work environment and the quality of education. However, conflict can also act as a catalyst for growth and innovation when managed constructively. This study utilizes a qualitative approach based on a literature review to identify effective conflict management strategies in PAUD. The results of the study indicate that strategies such as discussion and collaboration, compromise, mediation, and conflict management training are crucial in creating a harmonious work environment. Furthermore, building a culture of open communication, team cooperation, and fair conflict resolution is also essential. Effective conflict management has a positive impact on the performance of the educator team, enhancing communication and cooperation, reducing stress, and creating a conducive work environment. Consequently, wise leadership and the implementation of appropriate conflict management strategies are vital to creating a productive PAUD environment that supports the development of young children."